One-Pot Synthesis of Tetrasubstituted Imidazoles Catalyzed by Preyssler-Type Heteropoly Acid - Ali Javid; Majid M. Heravi; F. F. Bamoharram; Mohsen Nikpour (E-Journal of Chemistry)
A simple one-pot four-component synthetic method was reported for the preparation of tetrasubstituted imidazole derivatives from benzil, aromatic aldehydes, primary amines and ammonium acetate in the presence of Preyssler-type heteropoly acid catalyst. This method was proved to be eco-benign, easy work-up, convenient, relatively short reaction times and the products were isolated with high yields.